Pengaruh Konflik Kerja-Keluarga Terhadap Komitmen Organisasional Yang Dimediasi Oleh Kepuasan Kerja Pada Profesi Perawat Di Rumah Sakit Umum Daerah (RSUD) Dr. Moewardi Surakarta - Renny Rantika; Sunjoyo Sunjoyo (Universitas Airlangga, 2011)
The aim of this study is to examine whether work family-conflict affects the organizational commitment mediated by job satisfaction in the nursing profession. The survey is done at Rumah Sakit Umum Daerah (RSUD) Dr. Moewardi Surakarta. The subjects of this study are 152 of 154 nurses. The outliers, validity, reliability, descriptive statistic and interconstruct correlation test were conducated before hypotheses test. Path analysis was used to examine five hypotheses. The results show that two hypotheses were supported and three hypotheses were not supported. In the short, work interfering with the family negatively affects on job satisfaction and job satisfaction positively affects organizational commitment. The implications of this study were discussed and the suggested research will be advanced during the process.